Clinical presentation, diagnosis, and treatment of chronic granulomatous disease - Staudacher, Olga; von Bernuth, Horst (Frontiers in Pediatrics, 2024)
Chronic granulomatous disease (CGD) is caused by an impaired respiratory burst reaction in phagocytes. CGD is an X-linked (XL) (caused by pathogenic variants in CYBB) or autosomal recessive inborn error of immunity (caused by pathogenic variants in CYBA, NCF1, NCF2, or CYBC1). Female carriers of XL-CGD and unfavorable lyonization may present with the partial or full picture of CGD. Patients with CGD are at increased risk for invasive bacterial and fungal infections of potentially any organ, but especially the lymph nodes, liver, and lungs. Pathogens most frequently isolated are S. aureus and Aspergillus spp. Autoinflammation is difficult to control with immunosuppression, and patients frequently remain dependent on steroids. To diagnose CGD, reactive oxygen intermediates (O2− or H2O2) generated by the NADPH oxidase in peripheral blood phagocytes are measured upon in vitro activation with either phorbol-12-myristate-13-acetate (PMA) and/or TLR4 ligands (E. coli or LPS). Conservative treatment requires strict hygienic conduct and adherence to antibiotic prophylaxis against bacteria and fungi, comprising cotrimoxazole and triazoles. The prognosis of patients treated conservatively is impaired: for the majority of patients, recurrent and/or persistent infections, autoinflammation, and failure to thrive remain lifelong challenges. In contrast, cellular therapies (allogeneic stem cell transplantation or gene therapy) can cure CGD. Optimal outcomes in cellular therapies are observed in individuals without ongoing infections or inflammation. Yet cellular therapies are the only curative option for patients with persistent fungal infections or autoinflammation.